Genetic divergence in sesame based on morphological and agronomic traits - Arriel, Nair Helena Castro; Di Mauro, Antonio Orlando [UNESP]; Arriel, Eder Ferreira [UNESP]; Unêda-Trevisoli, Sandra Helena; Costa, Marcelo Marchi [UNESP]; Bárbaro, Ivana Marino; Muniz, Franco Romero Silva [UNESP] (My University, 2007)
The evaluation of diversity in germplasm collections is important for both plant breeders and germplasm curators to optimize the use of the variability available. Diversity can be estimated by different genetic markers. The purpose of this study was to estimate the genetic divergence of 30 morphological and agronomic traits in 108 sesame genotypes by multivariate analysis. The Cole-Rodgers index was used to establish the dissimilarity matrices. The principal component analysis identified the traits that contributed most to the divergence and the genotypes were clustered by Tocher's optimization. Despite the narrow genetic basis, the markers were efficient to characterize the genotypes and identify the most similar groups or duplicate and divergent genotypes. Greatest variation was found for the traits number of capsules per plant and grain yield.
Keywords: Genetic diversity; Germplasm; Multivariate analysis; Sesamum indicum L.; Sesamum indicum